Robotic process automation : RPA fundamentals and build a robot (Packt Publishing, 2019)
"Automation is driving a new way of working. In the time to come, workplaces will feature a blend of human and digital workers ('bots'), and this symbiotic relationship will create many new exciting career possibilities. Are you ready to seize the opportunities that arise as we move into this automated era? If not, now is a good time to get trained and certified in the most in-demand and high-paying skill for jobs of the future, Robotic Process Automation (RPA). Robotic Process Automation is a game-changing technology designed to automate high-volume, repeatable tasks that take up a large percentage of a worker's time. With this course, you'll get a clear overview of what RPA is, how it works, and when to apply it. You'll even gain hands-on experience building a robot that automates a simple business process in the UiPath Studio RPA software. This way, you'll understand the bigger picture and find out how the technology works in practice. Further, the course demonstrates how to pilot the technology in an enterprise setting so that you know what steps to take to succeed with any RPA initiative in your organization."--Resource description page